Emerging psychosocial factors and work overload perceptions of Mexican university teachers and students working and studying from home during the COVID-19 pandemic - Quezada Díaz, Belem; Hindrichs, Imke; Castellanos Simons, Doris (Frontiers in Psychology, 2024)
Introduction In Mexico, academic activities during the COVID-19 pandemic were conducted from home for over 2 years. Especially during the initial months of the pandemic, the lockdown conditions necessitated a reorganization and a new understanding of social dynamics. Therefore, this study aimed to explore the perceptions of university students and teachers regarding emerging psychosocial factors that either encouraged or hindered work and/or study from home during confinement, as well as their perceptions of work overload. Furthermore, the differences between students and teachers in the studied variables were analyzed. Method A predominantly quantitative, cross-sectional, and correlational study was conducted with 108 participants (42.6% university teachers; 57.4% graduate or postgraduate students) who filled out an online questionnaire encompassing two open-ended inductors to identify the positive and negative aspects of working or studying from home and their frequency of perceptions, the COVID-19 Work Overload from Home Scale (ESTC-COVID-19), and questions about the hours per day devoted to different activities. The open responses were categorized by two independent groups of the research team; the emerging categories were then consensually agreed upon and further transformed into dummy and continuous variables. These variables and the results of the ESTC-COVID-19 were analyzed with SPSS 19 using Pearson's correlation coefficient, the Chi-squared test, and Student's t-test. The results identified 9 positive and 10 negative emerging psychosocial factors attributed to at least 10% of the sample's open answers. In addition, work overload correlated negatively with the emerging factor of “Making better use of time” and positively with “Work, school, and/or domestic activities overload;” moreover, students perceived more work overload than teachers. Discussion Differences between students and teachers were observed in the following psychosocial factors: “Self-management,” “Comfort,” and “Enjoying home” (as positive factors) and “Domestic work” and “Interruptions, distractors, noise” (as negative factors), with students generally reporting more discomfort than teachers. The study analyzes these differences in relation to the demands and nature of the study and work activities undertaken by both groups, as well as the previous training of the skills and the resources required to carry them out.